Indikasi Jual Rugi untuk Menyingkirkan Pelaku Usaha Lainnya Berdasarkan Uu No. 5 Tahun 1999 tentang Larangan Praktek Monopoli dan Persaingan Usaha - Erica Flora; Elfrida Ratnawati (UNES Law Review, 2023)
In buying and selling activities on the TikTok application, many business actors sell goods below market price with the aim of getting rid of their competitors or other business actors. Are the actions of business actors who reduce prices below market with the aim of eliminating their competitors permitted in Law no. 5 of 1999 concerning Prohibition of Monopoly Practices and Business Competition? is the main problem of writing this research. The research method used is normative legal research, which uses secondary data and is analysed descriptively. The results of this research show that the actions of business actors who reduce prices below market with the aim of eliminating their competitors are prohibited according to the Business Competition Law, in the proof process using the approach rule of reason it is necessary to fulfil the elements of Article 20 of the Business Competition Law to be considered a selling practice at a loss. The flash sale program with the features live streaming in the TikTok application, is not necessarily a practice of selling at a loss carried out by business actors because it requires fulfilment of the elements, conditions, and validation of the sale of this practice.